Gambaran Pelayanan Informasi Obat (PIO) Terhadap Kepuasan Pasien di Apotek Afi Farma Bantul - Monik Krisnawati (Jurnal Indonesia Sehat, 2022)
Background: Drug information service is one of the pharmaceutical activities carried out by pharmacists. Provision of drug information is impartial, critically evaluated and with the best evidence in all aspects of drug use to other health professionals, patients or the public. Satisfaction is a customer's emotional reaction to the perceived service quality with the expected service quality. Patient satisfaction is a vitally indispensable indicator to improve drug information service. Purpose: The aim of this research is to determine patient satisfaction with drug information service at the Apotek Afi Farma. Method: This research was used the Quantitatif which is using the Cross Sectional Approach. The total respondent are 70 peoples. Data analysis was carried out using a quantitative descriptive analysis approach. Result: The results showed that the quality of Drug Information Services (PIO) at Apotek Afi Farma on the five dimensions had positive values, namely the dimensions of tangible, reliability, and responsiveness. On the other hand, the assurance and empathy dimensions show a zero value. Conclusion: Patients have been very satisfied with drug information services on the dimensions tangible, reliability, and responsiveness as well as satisfaction on the dimensions of assurance and empathy.